Green Organizational Culture as an Emerging Tren : A Bibliometric Analysis - Rosyanti, Daisy Marthina; Dewanti, Mentari Clara; Khoirotunnisa, Fani (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim : Conducting a literature review to examine the development of literature from the green culture variable so that a visual mapping is obtained that describes the interrelated relationship between green culture and environmental performance and other variables in several industrial sectors. Methode : This study employs a quantitative approach, utilizing time series data from the past decade along with bibliometric analysis. From the patterns and trends visualized, it can be known the relationship or correlation between various related factors. Research Finding : Organizational culture still dominates as a fundamental aspect of green organizational performance, although recent trends point to the broader evolution of the concept of "green" when referring to sustainability missions. Regardless of where the organization is on their journey to sustainability, organizational culture remains key to ensuring that eco-friendly policies and practices can be successfully integrated within all elements of the organization. Theoretical contribution/Originality : This study contributes to enriching the literature and improving understanding of how green culture affects organizational structures and processes. Practitionel/Policy implication : The literature on green culture has not been widely researched, this may be because the practice of green cultural transformation is still limited in the field. However, this consensus has great potential to grow as attention to sustainability and environmental responsibility in various sectors, both profit and public sector